(Un)representing Belarus(ianness): Ihar Babkoŭ's Adam Klakotski and His Shadows (2001). Issue 2 (3rd July 2022) - Ghilarducci, Manuel
ABSTRACT: National identity discourses and narratives of history and memory are highly politicized in post-Soviet Belarus. While official narratives stress the idea of brotherhood with Russia and the importance of the Soviet cultural legacy, counter-narratives focus on the idea of a national revival and on mourning for the pre-Soviet past. In the late 1990s and early years of the new millennium, authors of counter-narratives began to work with philosophical models in their rethinking of "Belarusianness." The peak of this philosophical turn was marked by Ihar Babkoŭ's Adam Klakotski and His Shadows (2001). Under the influence of post-colonial theory and post-structuralist/deconstructive philosophy, and with the help of narrative fragmentation devices, the novel proposed a unique reconceptualization of Belarusianness. Based on the assumption that every identity has a negative fundament, Adam Klakotski deconstructs the linearity of national(ist) narratives on different levels. In this article, the author analyzes the philosophical aspects of Adam Klakotski and the role the novel has played politically, and he compares it to the works of two other key figures of Belarusian counter-culture: Little Guidebook to the Sun City by Artur Klinaŭ, and Valiantsin Akudovich's There Is No Me and The Code of Absence .